2015
DOI: 10.1039/c4an01602e
|View full text |Cite
|
Sign up to set email alerts
|

Novel l-lactic acid biosensors based on conducting polypyrrole-block copolymer nanoparticles

Abstract: The development of advanced nanomaterials for the highly efficient electrical detection of biological species has attracted great attention. Here, novel polypyrrole-Pluronic F127 nanoparticles (PPy-F127 NPs) with conducting and biocompatibility properties were synthesized and used to construct a L-lactic acid biosensor that could be applied in biochemical assays. The PPy-F127 NPs were characterized by transmission electron microscopy (TEM), elemental analysis and UV-vis spectroscopy. Lactate oxidase (LOx) stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…The reported biosensor had good electrocatalytic activity toward L-lactic acid with a linear range of 15μM-37.5 mM and a low detection limit of 8.8 μM. The L-lactic acid biosensor had also a good anti-interference property toward uric acid, ascorbic acid, glucose, and cysteine [51].…”
Section: Biosensorsmentioning
confidence: 86%
See 1 more Smart Citation
“…The reported biosensor had good electrocatalytic activity toward L-lactic acid with a linear range of 15μM-37.5 mM and a low detection limit of 8.8 μM. The L-lactic acid biosensor had also a good anti-interference property toward uric acid, ascorbic acid, glucose, and cysteine [51].…”
Section: Biosensorsmentioning
confidence: 86%
“…Sun et al have recently reported polypyrrole-Pluronic F127 nanoparticles (PPy-F127 NPs), a novel conducting polymer nanomaterial [51]. These novel nanomaterials were employed in the design of biosensors, which were further used in biochemical assays of L-lactic acid in pig muscle samples.…”
Section: Biosensorsmentioning
confidence: 99%
“…The combination of biomolecules with block copolymers turns the nanoassemblies reviewed in this article into prime candidates for a broad range of biomedical applications, notably as biosensors (Islam et al, 2014; Sun et al, 2015; Idrissi et al, 2018), in diagnostic imaging (Choi et al, 2012; Mi et al, 2017; Quader and Kataoka, 2017), as drug/gene delivery systems, mainly in the context of cancer treatment (Nishiyama et al, 2016; Quader and Kataoka, 2017; Varela-Moreira et al, 2017; Cabral et al, 2018; Cheng et al, 2018; Mukerabigwi et al, 2018; Wang et al, 2018a; Wang J. et al, 2018), in the treatment of infectious disease (Aderibigbe, 2017; Liu et al, 2017) and the fight against biofilms (Liu et al, 2018), and in regenerative medicine (Torabinejad et al, 2014; Mota et al, 2015; Raisin et al, 2016; Susanna et al, 2017; Rey-Rico and Cucchiarini, 2018).…”
Section: Present and Future Perspectives On Biomedical Applicationsmentioning
confidence: 99%
“…These types of sensors are experimentally proved to be effective in detecting alcohol, glucose, immunoglobulin G, anions, cations, volatile organic gases etc., as reported from massive studies in the literature. As examples, the design and fabrication of some specific sensors using polypyrrole can be found in [8][9][10][11][12][13][14][15], just to name a few. The review articles in [3][4][5][6] are excellent works to discuss some recent developments and sample works for biomedical related applications.…”
Section: Introductionmentioning
confidence: 99%